Exchange of new ideas: towards a more open, cooperative and sustainable world - Johannes Platje; Grahame Fallon; Mehmet Baha Karan; Wim Westerman; Yoram Krozer; Markus Will; Katarzyna Kurek; Johan van Ophem (The Central European Review of Economics and Management (CEREM), 2020)
Aim: Provide a summary of the expressed views, presentations and discussions during the ISINI14 (2020) online conference. Design: Next to rather traditional but this time online presentations, the discussions not only took place by way of oral communication, but also via an online tool. The administrators of the conference prepared in a word-processing programme a framework, where the participants could enter issues, questions and comments in real time, and react to each others writings. These issues, questions and comments were also discussed orally. The results of the exchange of new ideas are presented below, and should provide an impulse for further discussion at~ ISINI online meetings in the future. Findings: In order to achieve sustainable development, protect democratic values and empower citizens in different countries with a different institutional setting, a sound balance between open markets and sound regulation should be struck at various levels. Global and regional (EU) cooperationis needed for solving challenges to sustainable development - e.g. in relation to unexpected events such as the COVID-19 pandemic and ~climate (change) as a kind of public good.
Keywords: D70; D81; F02; Q01; Q54; 330; new ideas; empowerment; climate change; COVID-19; European Union; decision making process; risk management; sustainable development